Gravitational rainbow - Accioly, A.; Blas, H. (American Physical Soc, 2001)
It is shown that, unlike Einstein's gravity, quadratic gravity produces dispersive photon propagation. The energy-dependent contribution to the deflection of photons passing by the Sun is computed and subsequently the angle at which the visible spectrum would be spread over is plotted as a function of the R-mu nu(2)-sector mass.